2020
DOI: 10.2147/ahmt.s238603
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pre-Transition Readiness in Adolescents and Young Adults with Four Chronic Medical Conditions in South East Nigeria – An African Perspective to Adolescent Transition</p>

Abstract: Introduction:When a child reaches a certain age, he or she moves over to the adult physician. For this to maximally benefit the child, there has to be a process of equipping the child with skills required for taking on more responsibilities. Transitioning involves a process in which the adolescent with chronic illness is prepared ahead of time to enable them to eventually transfer to adult care with good outcomes. In high-income countries with wellorganized health financing, the transitioning process begins as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Regardless of whether they received preparation, participants reported satisfaction with the overall transition experience and their care at the adult SCD clinic. This perspective contrasts US-based and Nigeria-based studies of AYAs with SCD, where most participants preferred their pediatric clinic as a source of SCD care 14,19,25. These differences may in part be attributable to variations in age of transfer and patient experiences about accessibility and quality of adult care.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Regardless of whether they received preparation, participants reported satisfaction with the overall transition experience and their care at the adult SCD clinic. This perspective contrasts US-based and Nigeria-based studies of AYAs with SCD, where most participants preferred their pediatric clinic as a source of SCD care 14,19,25. These differences may in part be attributable to variations in age of transfer and patient experiences about accessibility and quality of adult care.…”
Section: Discussionmentioning
confidence: 90%
“…This perspective contrasts US-based and Nigeria-based studies of AYAs with SCD, where most participants preferred their pediatric clinic as a source of SCD care. 14,19,25 These differences may in part be attributable to variations in age of transfer and patient experiences about accessibility and quality of adult care. To our knowledge, prior studies assessing the impact of transition preparation for patients with SCD on experiences or other outcomes in SCD in Africa have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The STARx tool was validated by Ferris et al for adolescents with various chronic conditions in the US and [ 17 ], although not yet adapted, is used in different countries, such as Nigeria [ 49 , 50 ]. Ayuk et al measured the pre-transition readiness of Nigerian adolescents with various chronic illnesses and concluded that regardless of age, transitional readiness and willingness were suboptimal [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The STARx tool was validated by Ferris et al for adolescents with various chronic conditions in the US and [ 17 ], although not yet adapted, is used in different countries, such as Nigeria [ 49 , 50 ]. Ayuk et al measured the pre-transition readiness of Nigerian adolescents with various chronic illnesses and concluded that regardless of age, transitional readiness and willingness were suboptimal [ 49 ]. Eluri et al gathered that patients with eosinophilic esophagitis and eosinophilic gastroenteritis were less aware of the transition and their transition readiness was below that of patients with different conditions [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in low and middle income countries (LMIC) have investigated the transition to adult care of adolescents with chronic medical conditions such as sickle cell disease and asthma [23][24][25]. A few studies involving ALHIV have focused on transition readiness assessment [26], patient and healthcare providers' perspectives on transition and some have investigated transition programs [12,27].…”
Section: Introductionmentioning
confidence: 99%